Trust in Medical Research: A comparative study among Patients at a Regional Referral Hospital and Community Members in Lira District, Northern Uganda - Pulle, Jafesi; Loue, Sana; Kiwanuka, Gertrude N.; Francis, Bajunirwe (Journal of Empirical Research on Human Research Ethics, 2024)
Events such as the Tuskegee syphilis study shaped how the public perceives and trusts medical research globally. However, few studies have examined trust in medical research in developing countries. We tested the hypothesis that levels of trust may be lower among community members compared to hospitalized persons in Uganda. We enrolled 296 participants in rural northern Uganda, and 148(50%) were from the community, 192(65%) were female. Mean level of trust for medical research was higher among hospitalized persons compared to community members (p=0.0001). Previous research participation (p=0.03), and willingness to participate in future research (p=0.001) were positively associated with trust. Medical personnel should engage more with the communities in which they practice fostering trust in medical research
Keywords: Trust; Medical Research; Research Ethics; CBPR; Research Ethics; RCR